A new Peritrich Ciliate from a Hypersaline Habitat in Northern China - Zhuang, Yuan; Clamp, John C.; Yi, Zhenzhen; Ji, Daode (Zootaxa, 2016)
A new peritrichous ciliate, Cothurnia salina n. sp., collected from a brine pond of a salt factory in Yantai, China, was investigated based on live observations, silver staining method and molecular phylogenetic analysis. The diagnosis for this new taxon: body elongated columnar, in vivo 80–98 × 12–19 µm; lorica barrel-shaped, with aboral part heavily thickened; stalk extremely short, with approximately ½ of its length within the lorica; macronucleus wormlike, longitudinally oriented; single contractile vacuole ventrally located; pellicle with conspicuous parallel transverse striations, 62–73 from aboral trochal band to peristome and 32–38 from aboral trochal band to scopula; infundibular polykinety 3 (P3) consisting of two ciliary rows, which are equal length, parallel to each other and terminate adstomally between P1 and P2. Small subunit (SSU) rRNA gene trees revealed that the new species clustered with other members of the family Vaginicolidae as expected.